Linkage Investment Opportunity Set (IOS) with Financial Policy in Growing Companies in Indonesia Stock Exchange (BEI) - Mrs Marheni (Fakultas Ekonomi, Universitas Bangka Belitung, 2018)
The aims of this study were to analyze the influence of disclosure policy, funding policy, dividend policy on IOS and to analyze the difference of IOS influence on disclosure policy, fund policy and dividend policy in the company grow and not grow. The population in this study were companies listed on the Indonesia Stock Exchange there are 509 companies. The sample was chosen by purposive sampling method as many as 88 companies. Methods of data analysis used multiple linear regression analysis and independent t-test. The result of data analysis shows that the company disclosure policy has no effect on IOS. Funding policies as measured by Book Debt Equity companies had a significant effect on IOS. The dividend policy measured by the House of Representatives had no significant effect on IOS. There were IOS differences, disclosure policies, funding policies and dividend policies in the company growing and not growing.